Unification of concepts by Paraconsistent Logic and Rescheduling, Pre-scheduling of Surgeries (Queue of Elective Orthopedic Surgeries) for decision making (Research, Society and Development, 2022)
During the Surgery Scheduling process, there is a need to request materials and shipments, as those involved are supplying companies, as well as confirmation and understanding of what was requested. The lack of an item can lead to cancellation, causing a rescheduling, a new allocation of the surgical team. The problem raised continues in the inconvenience to the patient, hospital, and to health insurance, as there is a constant need for a new release for surgery. The analyzed process study refers to elective (scheduled) orthopedic surgeries. In this context, Logic Eτ concepts are studied for decision- making in the Elective Orthopedic Surgery Agenda problem, mainly because in the cancellation due to lack of instruments and consigned material, measures are taken before anesthetizing the patient. It is understood because of the unification of concepts to meet the decision-making in the procedure for canceling elective orthopedic surgery.